A Modified Methodology for Calculating Regional Forest Fire Hazard Scales - Roman V. Kotelnikov; Alexandеr A. Martynyuk (Лесной журнал)
Weather conditions are one of the most important factors affecting forest fire hazard. In Russia, it is the indices characterizing the fire hazard in forests depending on weather conditions that are traditionally used to regulate the work of forest fire services. In particular, the fire hazard class, the calculation method for which (based on the developments by V.G. Nesterov) has been approved by the order of the Federal Forestry Agency, is used to calculate the frequency of aviation patrols of forests. Taking into account the different densities of weather stations in different years, several modifications of this method have been developed, such as PV-1, PV-2, PVG, but only the Nesterov method is officially approved, despite a number of disadvantages. The accumulation of large volumes of structured data, as well as the development of information technologies, makes it possible to optimize existing approaches to calculating the boundary values of a complex fire hazard index in forests and, for the first time, to perform detailed calculations for all regions of the Russian Federation. Thus, prerequisites have arisen in Russia for updating the regulatory legal framework in this area. The proposed modified methodology is based on the classical principle of assessing the boundaries of classes in the fire hazard scale, corresponding to the proportion of forest fires that occur: 5, 20, 45 and 70 %. At the same time, the fundamental new feature is the choice (based on a numerical criterion) of the methodology that is most suitable for a specific territory. In this case, it is proposed to use the Nesterov and PVG method in a modified version (with temperature and dew point values for yesterday with updated precipitation data: day/night). This paper substantiates that such changes will not significantly affect the adequacy of the index, while allowing calculations to be made for the morning of the current day, which is necessary for practical application. Another important feature has been the transition to a weighted average calculation of indices. The subject of the Russian Federation as a whole has been selected as a unit of calculation for regions with small forest areas. Large regions have been divided along the boundaries of forest areas. For the subjects of the Russian Federation with pronounced intra-seasonal fluctuations in fire frequency index, the scales have been calculated separately for characteristic periods. To visualize the scales obtained during the study, a special interactive web service has been developed, which has significantly simplified the process of monitoring and interpreting the results. The proposed scales can be used to improve the regulatory framework in the field of forest fire protection.